The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Collaborating across mountains: contributions of the Mountain Invasion Research Network (MIREN) to ecology and conservation - Aníbal Pauchard; Eduardo Fuentes-Lillo; Jake Alexander; Manzoor A. Shah; Agustina Barros; Lohengrin Cavieres; Sylvia Haider; Jonas J. Lembrechts; Keith McDougall; John W. Morgan; Vincent Ralph Clark; Irfan Rashid; et al. (Biological Invasions, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Beyond the Trail—Understanding Non‐Native Plant Invasions in Mountain Ecosystems - Agustina Barros; Eduardo Fuentes Lillo; Valeria Aschero; Aníbal Pauchard; María Alisa Alvarez; Ronja Wedegärtner; Jan Clavel; Jana Müllerová; Jan Pergl; Shengwei Zong; Michaela Vítková; Tereza Klinerová; et al. (Global Ecology and Biogeography, 2025)
Aim We aimed to examine the abiotic, biotic and anthropogenic drivers of non‐native plant species distribution along hiking trails in mountainous regions. Location Nine mountain regions across six continents, including North America (USA), South America (Argentina and Chile), Europe (Sweden, Norway, Czech Republic), Africa (South Africa), Asia (China) and Oceania (Australia). Time Period Data were collected between 2016 to 2022 during the summer season. Major Taxa Studied Vascular plants. Methods We implemented a standardised sampling design (MIREN trail survey) with T‐shaped sample sites placed parallel to trails and perpendicular to adjacent vegetation. We examined the main drivers (abiotic, biotic and anthropogenic factors) affecting non‐native species' presence, richness and cover. Results At the global scale, abiotic (climatic) variables explained most of the variation in non‐native species richness. In contrast, biotic factors were the most important for the presence and cover of non‐native plants. Anthropogenic factors, including distance to the trail, use intensity and livestock grazing, were also important but to a lesser extent than the main factors. While the total number of non‐native species differed across regions, the patterns explaining plant invasions were consistent. Main Conclusions Our regional study identified mountain trails that are particularly vulnerable to plant invasions. Our findings suggest that under future scenarios of climate change, increased anthropogenic pressure and heightened livestock activity, the presence of non‐native species beyond trail edges may become more frequent. This highlights the need to restrict off‐trail activities in areas of high conservation value.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Biochemical and molecular biomarkers and their association with anthropogenic chemicals in wintering Manx shearwaters (Puffinus puffinus) - Patricia P. Serafini; Bárbara P.H. Righetti; Ralph E.T. Vanstreels; Leandro Bugoni; Clei E. Piazza; Daína Lima; Jacó J. Mattos; Cristiane K.M. Kolesnikovas; Alice Pereira; Marcelo Maraschin; Isadora Piccinin; Tim Guilford; et al. (Marine Pollution Bulletin, 2024)

Biomasonry products from macroalgae: A design driven approach to developing biomaterials for carbon storage - Kate Scardifield; Nahum McLean; Unnikrishnan Kuzhiumparambil; Peter J. Ralph; Nicolas Neveux; Geoff Isaac; Tim Schork (Journal of Applied Phycology, 2024)
Lowering the embodied carbon of building materials requires a transition away from fossil derived products towards bio-based alternatives, alongside the design and development of new clean tech biomaterials that can function as carbon sinks. This paper presents an overview of historical and existing uses of seaweeds in construction to identify gaps and opportunities for the development of seaweed-based construction materials that can support atmospheric carbon removal through algal photosynthesis. This study highlights the value of interdisciplinary research collaborations that can be situated within the expanding field of biodesign where design research and methods are used to influence the development materials science. It presents as a case study the design of seaweed bricks utilising a biorefinery framework that aims to valorise residual seaweed biomass being grown for waste-water management, identifying value-adding opportunities for this seaweed by-product and new possibilities for carbon storage in the built environment. It details the development of a 1:1 scale prototype for the purposes of an exhibition at the Art Gallery of South Australia in order to demonstrate what biomasonry products from macroalgae can look like, to build social acceptance and to encourage future uptake of sustainable seaweed construction products.

Research on biodeteriotration of plastics - Ji-Dong Gu; Tim Ford; Bryce Mitton; Ralph Mitchell (International Biodeterioration & Biodegradation, 2024)

Tradable planning permits in the field: Executive experimental results from Germany - Ralph Henger; Tim Straub; Christof Weinhardt (Land Use Policy, 2023)

Ecological consequences of historic moorland ‘improvement’ - Francis M. Rowney; Ralph M. Fyfe; Philip Anderson; Robert Barnett; William Blake; Tim Daley; Katie Head; Alison MacLeod; Ian Matthews; David N. Smith (Biodiversity and Conservation, 2022)

Wetlands in drylands: diverse perspectives for dynamic landscapes - Suzanne Grenfell; Michael Grenfell; Stephen Tooth; Adriana Mehl; Emily O’Gorman; Tim Ralph; William Ellery (Wetlands Ecology and Management, 2022)

Characterisation and Bioactivity Analysis of Peridinin-Chlorophyll a-Protein (PCP) Isolated from Symbiodinium tridacnidorum CS-73 - Kanoknate M. Supasri; Manoj Kumar; Anna Segečová; Janice I. McCauley; Andrei Herdean; Matthew P. Padula; Tim O’Meara; Peter J. Ralph (Journal of Marine Science and Engineering, 2021)
Peridinin-Chlorophyll a-Proteins (PCP) are the major light harvesting proteins in photosynthetic dinoflagellates. PCP shows great variation in protein length, pigment ratio, sequence, and spectroscopic properties. PCP conjugates (PerCP) are widely used as fluorescent probes for cellular and tissue analysis in the biomedical field. PCP consists of a peridinin carotenoid; thereby, it can potentially be used as a bioactive compound in pharmaceutical applications. However, the biological activities of PCP are yet to be explored. In this study, we extracted, purified, and partially characterised the PCP from Symbiodinium tridacnidorum (CS-73) and explored its antioxidant, anti-cancer and anti-inflammation bioactivities. The PCP was purified using an ÄKTA™ PURE system and predicted to be of 17.3 kDa molecular weight (confirmed as a single band on SDS-PAGE) with an isoelectric point (pI) 5.6. LC-MS/MS and bioinformatic analysis of purified PCP digested with trypsin indicated it was 164 amino acids long with >90% sequence similarity to PCP of SymA3.s6014_g3 (belonging to clade A of Symbiodinium sp.) confirmed with 59 peptide combinations matched across its protein sequence. The spectroscopic properties of purified PCP showed a slight shift in absorption and emission spectra to previously documented analysis in Symbiodinium species possibly due to variation in amino acid sequences that interact with chl a and peridinin. Purified PCP consisted of a 19-amino-acid-long signal peptide at its N terminal and nine helixes in its secondary structure, with several protein binding sites and no DNA/RNA binding site. Furthermore, purified PCP exhibited antioxidant and in vitro anti-inflammation bioactivities, and anti-cancer activities against human metastatic breast adenocarcinoma (MDA-MB-231) and human colorectal (HTC-15) cancer cell lines. Together, all these findings present PCP as a promising candidate for continued investigations for pharmaceutical applications to cure chronic diseases, apart from its existing application as a fluorescent-probe.

Unlocking the phylogenetic diversity, primary habitats, and abundances of free‐living Symbiodiniaceae on a coral reef - Lisa Fujise; David J. Suggett; Michael Stat; Tim Kahlke; Michael Bunce; Stephanie G. Gardner; Samantha Goyen; Stephen Woodcock; Peter J. Ralph; Justin R. Seymour; Nachshon Siboni; Matthew R. Nitschke (Molecular Ecology, 2021)
Dinoflagellates of the family Symbiodiniaceae form mutualistic symbioses with marine invertebrates such as reef‐building corals, but also inhabit reef environments as free‐living cells. Most coral species acquire Symbiodiniaceae horizontally from the surrounding environment during the larval and/or recruitment phase, however the phylogenetic diversity and ecology of free‐living Symbiodiniaceae on coral reefs is largely unknown. We coupled environmental DNA sequencing and genus‐specific qPCR to resolve the community structure and cell abundances of free‐living Symbiodiniaceae in the water column, sediment, and macroalgae and compared these to coral symbionts. Sampling was conducted at two time points, one of which coincided with the annual coral spawning event when recombination between hosts and free‐living Symbiodiniaceae is assumed to be critical. Amplicons of the internal transcribed spacer (ITS2) region were assigned to 12 of the 15 Symbiodiniaceae genera or genera‐equivalent lineages. Community compositions were separated by habitat, with water samples containing a high proportion of sequences corresponding to coral symbionts of the genus Cladocopium , potentially as a result of cell expulsion from in hospite populations. Sediment‐associated Symbiodiniaceae communities were distinct, potentially due to the presence of exclusively free‐living species. Intriguingly, macroalgal surfaces displayed the highest cell abundances of Symbiodiniaceae, suggesting a key role for macroalgae in ensuring the ecological success of corals through maintenance of a continuum between environmental and symbiotic populations of Symbiodiniaceae.

Transcriptomic investigation into polyketide toxin synthesis in Ostreopsis (Dinophyceae) species - Arjun Verma; Gurjeet S. Kohli; D. Tim Harwood; Peter J. Ralph; Shauna A. Murray (Environmental Microbiology, 2019)
Summary In marine ecosystems, dinoflagellates can become highly abundant and even dominant at times, despite their comparatively slow growth. Their ecological success may be related to their production of complex toxic polyketide compounds. Ostreopsis species produce potent palytoxin‐like compounds (PLTX), which are associated with human skin and eye irritations, and illnesses through the consumption of contaminated seafood. To investigate the genetic basis of PLTX‐like compounds, we sequenced and annotated transcriptomes from two PLTX‐producing Ostreopsis species; O . cf. ovata , O . cf. siamensis , one non‐PLTX producing species, O . rhodesae and compared them to a close phylogenetic relative and non‐PLTX producer, Coolia malayensis . We found no clear differences in the presence or diversity of ketosynthase and ketoreductase transcripts between PLTX producing and non‐producing Ostreopsis and Coolia species, as both groups contained >90 and > 10 phylogenetically diverse ketosynthase and ketoreductase transcripts, respectively. We report for the first‐time type I single‐, multi‐domain polyketide synthases (PKSs) and hybrid non‐ribosomal peptide synthase/PKS transcripts from all species. The long multi‐modular PKSs were insufficient by themselves to synthesize the large complex polyether backbone of PLTX‐like compounds. This implies that numerous PKS domains, including both single and multi‐, work together on the biosynthesis of PLTX‐like and other related polyketide compounds.

Correction to: Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd C. LaJeunesse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd LaJeunensse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Impact of nitrogen availability upon the electron requirement for carbon fixation in Australian coastal phytoplankton communities - David J. Hughes; Deepa Varkey; Martina A. Doblin; Tim Ingleton; Allison Mcinnes; Peter J. Ralph; Virginie van Dongen‐Vogels; David J. Suggett (Limnology and Oceanography, 2018)
Nitrogen (N) availability affects phytoplankton photosynthetic performance and regulates marine primary production (MPP) across the global coast and oceans. Bio‐optical tools including Fast Repetition Rate fluorometry (FRRf) are particularly well suited to examine MPP variability in coastal regions subjected to dynamic spatio‐temporal fluctuations in nutrient availability. FRRf determines photosynthesis as an electron transport rate through Photosystem II (ETR PSII ), requiring knowledge of an additional parameter, the electron requirement for carbon fixation ( K C ), to retrieve rates of CO 2 ‐fixation. K C strongly depends upon environmental conditions regulating photosynthesis, yet the importance of N‐availability to this parameter has not been examined. Here, we use nutrient bioassays to isolate how N (relative to other macronutrients P, Si) regulates K C of phytoplankton communities from the Australian coast during summer, when N‐availability is often highly variable. K C consistently responded to N‐amendment, exhibiting up to a threefold reduction and hence an apparent increase in the efficiency with which electrons were used to drive C‐fixation. However, the process driving this consistent reduction was dependent upon initial conditions. When diatoms dominated assemblages and N was undetectable (e.g., post bloom), K C decreased predominantly via a physiological adjustment of the existing community to N‐amendment. Conversely, for mixed assemblages, N‐addition achieved a similar reduction in K C through a change in community structure toward diatom domination. We generate new understanding and parameterization of K C that is particularly critical to advance how FRRf can be applied to examine C‐uptake throughout the global ocean where nitrogen availability is highly variable and thus frequently limits primary productivity.

Temperature oscillations may shorten male lifespan via natural selection in utero - Ralph A. Catalano; Tim A. Bruckner; Kirk R. Smith; Katherine B. Saxton (Climatic Change, 2012)

Effective generation of very low density lipoprotein receptor transgenic mice by overlapping genomic DNA fragments: high testis expression and disturbed spermatogenesis - Paul J. Tacken; Andre van der Zee; Tim L. Beumer; Ralph J. Florijn; Marion J. J. Gijpels; Louis M. Havekes; Rune R. Frants; Ko Willems van Dijk; Marten H. Hofker (Transgenic Research, 2001)